Generic Enterprise Architecture Model Design for Operational Management in Indonesian Ports: A Case Study of PT Integrasi Logistik Cipta Solusi (ILCS) - Daniel , Muhammad; Purwandari, Betty; Satria, Riri; Putro, Prasetyo (AI Society & STMIK Indonesia, 2025)
Ports serve as the backbone of trade and Logistics in Indonesia, supporting integration and efficiency through digital transformation. However, the absence of a generic Enterprise Architecture framework has led to system and process fragmentation, hindering cross-Stakeholder integration within the maritime sector. This study AIms to design a generic Enterprise Architecture model for port operational management in Indonesia using the TOGAF framework. The methodology employed includes needs analysis, interviews, document reviews, and observations. The scope of the research covers the Preliminary phase through to the Technology Architecture phase within the TOGAF ADM cycle. The results of the study include an Enterprise Architecture design focused on integration standards, process efficiency, and system interoperability. This model is expected to serve as a strategic guide for PT Integrasi Logistik Cipta Solusi (ILCS) in aligning information technology with the business needs of national ports.